ANALISIS DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN SOSIAL ANAK KELAS IV DI SDN 6 SINGKAWANG - Jumi Suherni; Rini Setyowati; Mertika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
JUMI SUHERNI: Examining the Effects of Technology Use on the Social Development of Fourth Grade Students at SDN 6 Singkawang. ISBI Singkawang, 2024. Thesis. The purpose of this study is to: 1) Assess the effect that children in Class IV at SDN 6 Singkawang have when using gadgets; and 2) Describe the social development of the students in Class IV at SDN 6 Singkawang. A case study research strategy is employed in conjunction with qualitative research methodology. Seven fourth-grade pupils, seven parents, and the class instructor served as the research subjects. Interviews and documentation served as the research's primary data collection methods. The data analysis method makes use of Miles and Huberman's analysis method, which includes the following data collecting,1) Using electronics in class IV at SDN 6 Singkawang has a detrimental effect. The findings of the study indicate that most kids just use their devices for play, even though kids should use them as educational tools. Parental monitoring is needed in this situation. 2) A consequence of children's use of devices is the gradual decline in their social development. In order to facilitate socialization, children should play more with friends and engage in outdoor activities as part of their social development.